Peran Citizen Reporter dalam Mendorong Partisipasi Publik melalui Media Sosial: Perspektif Administrasi Publik Partisipatif - Hardiyanti (Arus Jurnal Sosial dan Humaniora, 2025)
This paper examines the phenomenon of citizen reporters as a form of alternative political participation in the digital space, particularly through social media platforms. Within the framework of participatory public administration, the role of citizens in producing and distributing political information reflects a shift in how the public engages in democratic processes. Employing a literature review method, this study explores technological affordances, platform architectures, and their contribution to shaping alternative discursive spaces. The findings indicate that citizen reporters not only broaden access to political information but also provide participatory opportunities for marginalized groups excluded from mainstream media. Social media platforms such as Twitter and Facebook serve as crucial channels for civic expression and reduce gatekeeping hierarchies in information dissemination. By analyzing the role of citizen reporters through the lens of alternative journalism, this paper emphasizes the need to understand digital participation as a novel form of citizen engagement in public governance. The study supports the argument that digital platforms are not merely communication tools but have become socio-political infrastructures that enable the democratization of information and the institutionalization of participatory public spaces.